The Local Wisdom of Awik-awik in Marine Conservation in Sekotong, West Lombok, West Nusa Tenggara, Indonesia - Mohammad Liwa Irrubai; Subki (Jurnal Penelitian Pendidikan IPA, 2024)
This article explains that all this time, the utilization of the marine in West Sekotong Village, West Lombok, West Nusa Tenggara always happens and it disturbs it’s balance. For example, fishing by using fish bombs causes the destruction of coral reefs and the death of marine life. To prevent this exploitation, the community implements the local wisdom of Awik-awik in sea conservation. This research uses a qualitative approach and ethnographic research methods. Data collection: participant observation, in-depth interviews, and documentation. Data analysis used Miles and Huberman. The results show that since 2000, the people of West Sekotong Village in collaboration with Australian Baywach and the Fisheries Departement of West Lombok have planted 1,000 coral reefs by using iron frames. The contents of the awik-awik made in 2018 are: four kinds of orders or recommendations, and two kinds of punishment. The values of awik-awik are: the value of cooperation, honesty, discipline, care for the environment, and responsibility. The benefits after the implementation of awik-awik consist of five kinds, one of them is the maintenance of coral reefs in the West Sekotong area.